2012
DOI: 10.1590/s1982-56762012000500010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do extrato de alga e da argila silicatada na severidade da alternariose e na produtividade da cebolinha comum (Allium fistulosum L.)

Abstract: RESUMOA alternariose é uma das doenças mais importantes da cebolinha em cultivo orgânico. Assim, o objetivo deste trabalho foi avaliar o efeito de pulverizações semanais de argila silicatada (Rocksil ® ) e extrato de Ulva fasciata no controle da doença e produtividade da cebolinha neste sistema de cultivo. Avaliou-se a severidade final e a área abaixo da curva de progresso da doença nas folhas centrais (Yf e AACPDf), bem como da planta inteira (Yp e AACPDp). Na colheita, determinou-se o comprimento e peso fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…Thus, this polysaccharide may be efficient against necrotrophic pathogens, because this pathway is generally involved in defense responses against these pathogens (Glazebrook, 2005;Araújo et al, 2012). However, it was also demonstrated that ulvan can control biotrophic (Borsato et al, 2010;Paulert et al, 2010) and hemibiotrophic fungi (Paulert et al, 2009;Freitas & Stadnik, 2012).…”
Section: Ulvansmentioning
confidence: 99%
“…Thus, this polysaccharide may be efficient against necrotrophic pathogens, because this pathway is generally involved in defense responses against these pathogens (Glazebrook, 2005;Araújo et al, 2012). However, it was also demonstrated that ulvan can control biotrophic (Borsato et al, 2010;Paulert et al, 2010) and hemibiotrophic fungi (Paulert et al, 2009;Freitas & Stadnik, 2012).…”
Section: Ulvansmentioning
confidence: 99%
“…Foliar application of biostimulants that are based on seaweeds is an agrotechnical treatment that brought many advantages in numerous cultivations, including grapevine, watermelon, strawberry, apple, tomato, spinach, onion, bean, pepper, carrot, potato, wheat, corn, barley, rice, and turf grass. The results show that plants treated with lower concentrations of extract indicated a stronger growth, higher yield, and higher mineral and nutritive elements content relative to the control [28][29][30][31][32][33]. Positive reactions also included an improved flowering and fructification ability, product quality and efficiency, and resistance to abiotic stress [31,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Fuente: Elaboración propia El extracto de U. fasciata disminuyó la severidad nal (gura 1) y la ABCPE (gura 2) de mancha angular únicamente en los genotipos Mouro graúdo (52 %) e IPR Uirapuru (37 %), en los años 2005 y 2006, respectivamente. En estos genotipos, el efecto protector del extracto es semejante a lo relatado en otras enfermedades, como la antracnosis del frijol (Colletotrichum lindemuthianum) en 44 % (Abreu et al, 2008), la alternariosis (Alternaria porri) de la cebolla pequeña en 70 % (Araújo et al, 2012) de la vid, pepino y frijol, en niveles de 77, 80 y 90 %, respectivamente (Jaulneau et al, 2011). Sin embargo, Delgado et al (2013) no encontraron diferencias en la severidad de la mancha angular en el frijol, entre las plantas tratadas con el polisacárido algal ulvana (principal constituyente de las paredes celulares de esa alga).…”
Section: Resultados Y Discusiónunclassified
“…Por ejemplo, extractos acuosos de Ulva spp. reducen la severidad de la antracnosis (Colletotrichum lindemuthianum) del frijol en 44 % (Abreu et al, 2008), la alternariosis (Alternaria porri) de la cebolla pequeña en 70 % (Araújo et al, 2012), y de los oídios de la vid, pepino y frijol, en 77, 80 y 90 %, respectivamente (Jaulneau et al, 2011). Asimismo, aplicaciones preventivas de Ulva spp., aparte de proteger plantas de carretón (Medicago truncatula) del hongo Colletotrichum trifolii, pueden activar genes relacionados con la biosíntesis de toalexinas y de proteínas asociadas a la patogénesis y la pared celular (Cluzet et al, 2004).…”
Section: Introductionunclassified